The psychological state of students during the period of distance learning - Yu. V. Prilepko; M. S. Bakholdina (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with the actual problems of the impact of pandemic conditions on the psychological state of students. Various types of stress experienced by students during distance learning in a pandemic are described. The conditions leading to different types of stress of students are analyzed. The results of a study of the assessment of the psychological state of students during the period of distance learning, conducted among students of the North Caucasus Federal University in the direction of training 44.03.03 Special (defectological) education, are presented. Based on the experiment, conclusions are drawn about the necessary types of assistance to students experiencing stress due to the conditions of distance learning during the pandemic.